Shopping Facilities and Mobility Behaviour in East Germany: The Significance of Distance in the Choice of Store for Grocery Shopping - Achen, Matthias (European Journal of Transport and Infrastructure Research, 2005)
After the collapse of the socialist system, far-reaching structural changes took place in East Germany, with particular rapidity in two specific areas: in retailing with the trend towards large-scale outlets in peripheral locations, and in passenger transport with the trend towards longer journeys made by car. As far as attractive local retail facilities are concerned, it is important to establish what potential they have in this specific context with regards to both supply and demand. A closely linked issue is that of the significance of distance as a deter- mining factor in the choice of store for grocery shopping.